Multi-scale synergistic modification and mechanical properties of cement-based composites based on in-situ polymerization. (March 2023) - Yin, Bing; Hua, Xianle; Qi, Dongmei; Han, Kailu; Wang, Pan; Hou, Dongshuai; Liu, Chaohong
Abstract: For the multi-scale and multiphase composite structure, modifying cement-based material at different scales to improve structural and mechanical performance is necessary. This paper developed a continuous multi-scale synergistic modified cement-based material with excellent properties by polymers, whiskers, and fibers. Notably, the polymer network is formed by in-situ polymerization in the hydration process of cement and works in concert with different scales modified substances. Specifically, the effect of in-situ polymerization of acrylamide monomers (IPAM), calcium carbonate whiskers (CW), and polyvinyl alcohol (PVA) fibers on mechanical strength is analyzed by response surface methodology, and the optimal mix ratio design is obtained. With the optimized mix ratio, the flexural strength of multi-scale modification samples is increased by more than 135% compared to the neat paste, while the 28d compressive strength is maintained essentially the same, with only a 2.9% reduction. And multi-scale samples' properties are significantly improved compared to single-scale samples. In addition, multi-scale composites' mechanical properties and microstructure are characterized in detail to investigate the incredible performance and the modification mechanism. Three modified materials form a continuous micro- meso -macro multi-scale structure in the cement matrix. Moreover, the interaction between IPAM, CW, and PVA fibers is confirmed. The IPAM can in-situ modify the interfacial structure of fibers and whiskers, strengthen the interrelation between different scales, resulting in exciting enhancements of the cement-based composite's structure and performance. This multi-scale modification strategy provides new ideas and promising applications for preparing high-performance cement-based materials. Highlights: In-situ polymerization of acrylamide is applied to multi-scale modification. Micro- meso -macro multi-scale modified cement-based composite is developed. Response surface methodology is used to analyze and optimize. The toughness and flexural strength of multi-scale samples are greatly enhanced. Synergistic modification and interaction mechanisms are confirmed and investigated.